Deposits and processes on the tide-influenced fjord-head delta in Dicksonfjorden, Svalbard - Kvam, Maria Huse (UiT Norges arktiske universitet, 2018)
This study investigates for the first time the tide-influenced fjord-head delta in Dicksonfjorden, a fjord in central Spitsbergen, Svalbard. In order to examine the deposits and processes, sediment cores, surface observations and bulk samples have been obtained. Sedimentary facies, log transects and composite logs are presented. Sediment cores are dated with the 210Pb dating method to provide an average sedimentation rate for the intertidal zone. High-resolution aerial images are used to produce a geomorphological map of the area. Landforms and surface features are identified, described and interpreted. Sedimentological trends of the delta are described and interpreted. An aerial photo from 1938 is used to describe and discuss the development of the delta. Tidal flats, tidal channel, tidal bars, rill channels and cheniers are identified. 7 facies are identified which belong to tidal flat deposits or tidal bar deposits. The tidal flat deposits generally consist of muddy and sometimes sandy laminations, indicating mostly deposition from suspension during high tide. Deformational structures are common and together with circular depressions on the tidal flats they indicate shore ice influence. The tidal bar deposits generally consist of cross-laminated and structureless sand, indicating rapid deposition from a relatively strong heavy sediment-laden current. Heterolithic horizontal laminations, bedforms, reactivation surfaces and desiccation cracks together serve as a strong indicator of tidal influence. The wave-protected setting in which the delta is situated allows a microtidal range to be sufficient for influencing the deposits. Tidal flat deposits transition from mud flat to mixed sand-mud flats moving in a channel-ward direction, indicating a decrease of tidal current speed due to friction against the tidal flat. 210Pb profiles indicate non-steady deposition in the intertidal zone and an average sediment accumulation rate of 0,3 cm/year during the last century. Rill channels develop on tidal flats due to ...